2009
DOI: 10.1158/0008-5472.can-09-0108
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Localization of Cyclic AMP-Responsive Element Binding Protein-Regulated Transcription Coactivator 2 Provides a Link between Obesity and Breast Cancer in Postmenopausal Women

Abstract: Epidemiologic evidence supports a correlation between obesity and breast cancer in women. AMP-activated protein kinase plays an important role in energy homeostasis and inhibits the actions of cyclic AMP-responsive element binding protein-regulated transcription coactivator 2 (CRTC2). In postmenopausal women, the cyclic AMP-responsive element binding protein-dependent regulation of aromatase is a determinant of breast tumor formation through local production of estrogens. The present work aimed to examine the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
112
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(122 citation statements)
references
References 51 publications
8
112
0
Order By: Relevance
“…In addition, its expression is regulated by oncogenes such as HER-2/neu and tumor suppressor genes including BRCA1, LKB1, and p53 (9,11,(13)(14)(15)(16)(17)(18). Germ line mutations in the TP53 gene, which encodes p53, lead to Li-Fraumeni Syndrome (LFS).…”
mentioning
confidence: 99%
“…In addition, its expression is regulated by oncogenes such as HER-2/neu and tumor suppressor genes including BRCA1, LKB1, and p53 (9,11,(13)(14)(15)(16)(17)(18). Germ line mutations in the TP53 gene, which encodes p53, lead to Li-Fraumeni Syndrome (LFS).…”
mentioning
confidence: 99%
“…2). 26 Consistent with this, we have shown that the CRTC2 mutant S171A remains in the nucleus and stimulates aromatase PII activity, whereas the S171D mutant remains in the cytoplasm and cannot stimulate PII activity. (S171 is the site of phosphorylation by AMPK.)…”
supporting
confidence: 80%
“…Elevated circulating estrogen levels, as a result of increased peripheral aromatization of androgens, have been indicated to underlie the association between obesity and a higher risk of breast cancer in postmenopausal women (Brown et al 2009, Brown & Simpson 2010). In the present study, we showed that both PI.4-and PII-driven aromatase transcription can be efficiently suppressed by MSA, leading to a marked downregulation of aromatase mRNA, protein, and thereby activity.…”
Section: Discussionsupporting
confidence: 57%
“…A number of transcription factors have been implicated in PII regulation, including LRH-1, CREB, CRTC2, ATF2, SF-1, C/EBPs, Jun, and several orphan nuclear receptors , Clyne et al 2002, Yang et al 2002, Sofi et al 2003, Ghosh et al 2008, Kijima et al 2008, Brown et al 2009). PI.4 is a TATA-less promoter that contains a glucocorticoid response element, Sp1-binding site, and an interferon-g activation site element (Zhao et al 1996b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation